Graphene oxide/reduced graphene oxide films as protective barriers on lead against differential aeration corrosion induced by water drops. Issue 11 (27th October 2020) - Ruben, Bartali; Zhang, Gaixia; Xin, Tong; Giorgio, Speranza; Victor, Micheli; Gloria, Gottardi; Michele, Fedrizzi; Filippo, Pierini; Shuhui, Sun; Nadhira, Laidani; Ana C, Tavares
Abstract : Graphene-based materials have demonstrated chemical stability and are very promising for protection against the corrosion induced by water on lead surfaces. Abstract : Graphene-based materials have demonstrated high chemical stability and are very promising for protection against the corrosion of metal surfaces. For this reason, in this work, protective layers composed of graphene oxide, reduced graphene oxide and their mixtures were investigated, respectively, against the corrosion of the surface of lead induced by water drops. The materials were deposited on a Pb surface from their suspensions using a Meyer rod. The surface chemical composition, morphology and structure of the coatings were studied by X-ray photoemission spectroscopy (XPS), scanning electron microscopy (SEM), atomic force microscopy (AFM) and stylus profilometry. Moreover, a specific methodology based on the evolution of the water contact angle with time was used to evaluate the reactivity of the lead surface. The results show that the graphene-based materials can form an efficient barrier layer against the degradation of the Pb surface and that the degradation process induced by water is reduced by more than 70%. Moreover, unexpectedly, the best protective performance was obtained using graphene oxide as the coating.